1984
DOI: 10.1002/jcp.1041180113
|View full text |Cite
|
Sign up to set email alerts
|

Secretory activity of hamster tracheal explants and isolated tracheal epithelial cells and the effects of cystic fibrosis serum

Abstract: Serum from cystic fibrosis patients has been shown by scanning electron microscopy to cause release of large quantities of mucus from the cultured tracheal rings of 3-4-month-old male Golden Syrian hamsters. In order to study this phenomenon on single cells, an epithelial (HTE) cell culture has been established from the hamster tracheal rings using the cell rescue method of Goldman and Baseman (1980a, In Vitro, 16:313). The cells were demonstrated to be epithelial by histochemical staining and immunofluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

1984
1984
1997
1997

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…Thus, after 6 hr there was a 2.2-fold difference between NHS and CFS, a 1.5-fold difference between NHS and HHS, and a 1.4-fold difference between HHS and CFS. These data confirm earlier work which demonstrated that the observed differences were statistically significant at P < 0.01 (Rudick et al, 1984). 45Ca2+ uptake When 45Ca2f influx was measured, there was very low uptake in the presence of NHS compared to that seen with CFS (Fig.…”
Section: Stimulation Of Hte Cell Secretionsupporting
confidence: 94%
See 3 more Smart Citations
“…Thus, after 6 hr there was a 2.2-fold difference between NHS and CFS, a 1.5-fold difference between NHS and HHS, and a 1.4-fold difference between HHS and CFS. These data confirm earlier work which demonstrated that the observed differences were statistically significant at P < 0.01 (Rudick et al, 1984). 45Ca2+ uptake When 45Ca2f influx was measured, there was very low uptake in the presence of NHS compared to that seen with CFS (Fig.…”
Section: Stimulation Of Hte Cell Secretionsupporting
confidence: 94%
“…The cells were routinely grown in 100-mm plastic culture dishes containing Ham's F12 medium supplemented with M retinoate and 10% fetal calf serum (FCS). Culture conditions have been previously reported (Rudick et al, 1984).…”
Section: Culture Of Hte Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Much interest in the culture of normal airway epithelial cells has stemmed from the potential usefulness of such systems in the study of carcinogenesis (1 8, 19), pulmonary disease (20), and microbial pathogenicity (2 1). In the present study the isolation and growth in culture of airway epithelial cells from the ferret are described.…”
Section: Ten Days Later the Cells Were Fixed In 10%mentioning
confidence: 99%